A Structural Model of Teacher Performance: Examining Empowerment, Self-Efficacy, Creativity, and Trust - Awaludin; Sri Setyaningsih; Rais Hidayat (International Journal of Technology and Education Research, 2026)
This study examines a structural model of teacher performance by positioning empowerment, self-efficacy, transformational leadership, and creativity as exogenous variables, with trust as a mediating variable. The purpose of this study is to analyze the direct and indirect effects of these variables on vocational high school teacher performance in Bogor Regency, Indonesia. A quantitative survey design was employed involving 175 teachers from 45 vocational high schools selected through multistage proportional random sampling. Data were analyzed using descriptive statistics and path analysis. The results indicate that all exogenous variables significantly influence teacher performance, both directly and indirectly through trust. The indirect effect analysis shows that empowerment (β = 0.016; t = 2.793; p < 0.01), self-efficacy (β = 0.021; t = 3.467; p < 0.001), transformational leadership (β = 0.018; t = 3.830; p < 0.001), and creativity (β = 0.060; t = 9.070; p < 0.001) have significant effects on teacher performance through trust, with creativity demonstrating the strongest mediating effect. These findings confirm trust as a critical mechanism for enhancing teacher performance. This study contributes to the development of an empirically validated trust-based teacher performance model and provides evidence-based implications for school leadership development and vocational education quality improvement policies.